High-strength flame-retardant polyamide 66 composite material as well as preparation method and application thereof
By adding components such as glass fibers, aminosilane coupling agents to the polyamide 66 composite material, the problem of the strength of the polyamide 66 composite material in the prior art is solved, and the combination of high strength and excellent flame retardant performance is achieved, and it is suitable for a variety of industrial fields.
Patent Information
- Application Number
- CN202411651488.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
While improving the flame retardant effect, existing polyamide 66 composite materials are difficult to maintain high strength and cannot meet the increasingly demanding environmental requirements.
The flame retardant and mechanical properties of the composite are improved by adding glass fibers, aminosilane coupling agents, 2-carboxyethylphenylphosphoric acid, metal hydroxides and synergistic flame retardants (such as aluminum trioxide or antimony trioxide) to the polyamide 66 resin.
It has achieved high strength and excellent flame retardant properties of polyamide 66 composite materials, and its vertical combustion level reaches V-0 level, which is suitable for industrial fields such as automobiles, construction, and aerospace.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyamide 66 composite materials, and in particular to a high-strength flame-retardant polyamide 66 composite material and a preparation method and application thereof. Background Art
[0002] Polyamide 66 (PA66), chemically known as poly(hexamethylene adipate), is a polymer material with excellent comprehensive properties, and has the advantages of high mechanical strength, wear resistance, and high temperature resistance. It is widely used in the production of tire cords, airbag yarns, filter cloths, ropes, fishing nets, industrial conveyor belts, automobiles, and electronic components. Polyamide 66 is a self-extinguishing polymer, with a vertical combustion rating of UL94 V-2 and a limiting oxygen index of 22%~24%. It has certain flame retardant properties, but it cannot meet the requirements of increasingly harsh use environments.
[0003] In the related art, in order to improve the flame retardant effect of polyamide 66, the blending flame retardant modification method is one of the main methods for flame retardant modification of polyamide 66. It is to directly add flame retardants (such as halogenated flame retardants, phosphorus flame retardants and inorganic flame retardants, etc.) and blend with polyamide 66 resin matrix to improve the flame retardant effect. It has the advantages of simple preparation method, low cost, and suitability for industrial production. It is the most widely used in practical applications. However, with the deepening of research, the disadvantages of the blending flame retardant modification method have gradually emerged. For example, directly adding flame retardants to polyamide 66 will sacrifice other performance indicators of polyamide 66. A larger amount of flame retardant is required to meet the flame retardant performance requirements during blending, and a larger amount of flame retardant will cause the strength of polyamide 66 to decrease, which is difficult to meet actual needs.
[0004] Based on this, how to obtain a polyamide 66 composite material with high strength and flame retardant effect has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a high-strength flame-retardant polyamide 66 composite material and its preparation method and application. The polyamide 66 composite material not only has excellent flame retardancy (vertical combustion grade reaches V-0), but also has excellent mechanical properties. Its tensile strength can reach more than 155.5 MPa and its bending strength can reach more than 180.5 MPa. It can be widely used in industrial fields such as automobiles, construction, and aerospace.
[0006] In a first aspect of the present invention, a polyamide 66 composite material is provided, wherein the raw materials for preparing the composite material include the following components: Polyamide 66 resin, glass fiber, aminosilane coupling agent, 2-carboxyethylphenylphosphorous acid, metal hydroxide, synergistic flame retardant, wherein the synergistic flame retardant is selected from any one of aluminum oxide and antimony trioxide.
[0007] The polyamide 66 composite material according to the embodiment of the present invention has at least the following beneficial effects: (1) The polyamide 66 composite material of the present invention has excellent flame retardant properties. The present invention uses polyamide 66 as a resin material, and through the coordinated combination of glass fiber, aminosilane coupling agent, 2-carboxyethylphenylphosphite, metal hydroxide, and synergistic flame retardant (such as aluminum trioxide or antimony trioxide), the vertical combustion level reaches V-0 level when a small amount of flame retardant (such as 2-carboxyethylphenylphosphite) is added to the polyamide 66 resin base, which is beneficial to saving preparation costs. In addition, metal hydroxides themselves also have a certain flame retardant effect. Metal hydroxides will release water during heating (such as aluminum hydroxide decomposing into aluminum oxide and water). These waters form steam under high temperature conditions, which helps to dilute the oxygen in the combustion area, thereby slowing down the propagation speed of the flame, and further promoting the improvement of the overall flame retardant properties of the composite material.
[0008] (2) The polyamide 66 composite material of the present invention has excellent mechanical properties. The present invention uses glass fiber as the main reinforcing filler and effectively improves the interface compatibility between the glass fiber and the polyamide 66 resin by adding components such as aminosilane coupling agent, 2-carboxyethylphenyl hypophosphorous acid, and metal hydroxide. The amino group in the aminosilane coupling agent can form a hydrogen bond with the amide group (-CONH-) in polyamide 66, and the silane group reacts with the siloxane group on the surface of the glass fiber to form a chemical bond. This double bond enhances the interfacial adhesion between the resin and the glass fiber. The 2-carboxyethylphenyl hypophosphorous acid contains a carboxyl polar group, which helps to increase the surface energy of the glass fiber, making it easier to be wetted by the polyamide 66 resin, thereby improving the wettability of the resin to the fiber and thus improving the interface strength.
[0009] In some embodiments of the present invention, the raw materials for preparing the polyamide 66 composite material include the following components by weight: 60-85 parts of polyamide 66 resin; Glass fiber 10~30 parts; 3-8 parts of aminosilane coupling agent; 5-10 parts of 2-carboxyethylphenyl hypophosphorous acid; 3~8 parts of metal hydroxide 1~5 parts of synergistic flame retardant.
[0010] In some embodiments of the present invention, the addition ratio of the 2-carboxyethylphenylphosphite, the metal hydroxide and the synergistic flame retardant is 1-10:1-4:1, preferably 4-8:1.5-3:1.
[0011] In some embodiments of the present invention, the glass fiber is an alkali-free glass fiber; preferably, the alkali-free glass fiber has a length of 8 to 12 mm and a single fiber diameter of 9 to 13 μm.
[0012] Using alkali-free glass fiber as reinforcing filler helps to improve the mechanical properties of polyamide 66 composite materials, and it is found that when using alkali-free glass fiber with a high aspect ratio in the preparation raw material system of the present invention, it exhibits more excellent mechanical properties, which is presumably due to the increase in the stress-bearing area of the alkali-free glass fiber. In addition, in terms of flame retardant effect, alkali-free glass fiber with a high aspect ratio also exhibits more excellent high-temperature stability.
[0013] In some more preferred embodiments of the present invention, the length of the alkali-free glass fiber is 3-15 mm, and the diameter of the single fiber is 8-15 μm.
[0014] In some embodiments of the present invention, the aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane and aminoethylaminopropylmethyldiethoxysilane.
[0015] The preparation raw material system of the present invention adopts an aminosilane coupling agent as a main reagent for improving the interfacial compatibility between glass fiber and polyamide 66 resin. The present invention finds that compared with conventional alkylsilane coupling agents, aminosilane coupling agents have a better effect on improving the interfacial compatibility of materials. It is speculated that this is because the aminosilane coupling agent contains amino functional groups, and these amino functional groups can form hydrogen bonds or covalent bonds with polar functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of other components, which helps to further improve the interfacial bonding strength and stability, so that the polyamide 66 composite material obtains more excellent mechanical properties.
[0016] In some embodiments of the present invention, the metal hydroxide is selected from at least one of aluminum hydroxide, calcium hydroxide, magnesium hydroxide and zinc hydroxide.
[0017] In the present invention, the metal hydroxide can not only be used as a reaction raw material for the phosphate of the flame retardant protective layer, but also, due to its certain corrosiveness, it helps to improve the surface roughness of the glass fiber and the polyamide 66 resin.
[0018] In some embodiments of the present invention, the particle size of the synergistic flame retardant is 1-20 μm.
[0019] A second aspect of the present invention provides a method for preparing the polyamide 66 composite material as described in any one of the first aspects, comprising the following steps: S1, mixing the polyamide 66 resin, aminosilane coupling agent, 2-carboxyethylphenyl hypophosphorous acid, metal hydroxide and synergistic flame retardant to obtain a mixture; S2, extruding the mixed material and the glass fiber using a twin-screw extruder.
[0020] The preparation method according to the embodiment of the present invention has at least the following beneficial effects: the present invention adopts a twin-screw extruder to prepare the polyamide 66 composite material, which has the advantages of high efficiency, uniformity and precise control, and is helpful to produce materials with excellent performance and high consistency. In some embodiments of the present invention, the extrusion process uses the mixed material as a feed port raw material and the glass fiber as a fiber feeding port raw material.
[0021] In some embodiments of the present invention, the temperatures of zones one to six of the twin-screw extruder are: 220-240°C, 260-280°C, 265-285°C, 265-285°C, 265-285°C, 260-280°C.
[0022] In some embodiments of the present invention, the screw speed of the twin-screw extruder is 350~550 r / min.
[0023] The third aspect of the present invention provides use of the polyamide 66 composite material as described in any one of the first aspects in the preparation of automobile or building materials.
[0024] Other features and advantages of the present invention will be set forth in the description which follows. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0026] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0028] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0029] Example 1 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 2 parts of aluminum oxide.
[0030] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0031] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0032] Example 2 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 25 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 6 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 2 parts of aluminum oxide.
[0033] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0034] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0035] Example 3 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 6 parts of 2-carboxyethylphenylphosphite; 3 parts of aluminum hydroxide; 2 parts of aluminum oxide.
[0036] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0037] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the mixture to the feeding port of a twin-screw extruder, weigh the alkali-free glass fiber in the above-mentioned weight proportions and add the fiber through the fiber feeding port, and extrude the fiber from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0038] Example 4 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 1 part of aluminum oxide.
[0039] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0040] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0041] Example 5 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 5 parts of 2-carboxyethylphenylphosphite; 5 parts of aluminum hydroxide; 3 parts of aluminum oxide.
[0042] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0043] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0044] Example 6 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 2 parts of aluminum oxide.
[0045] Among them, the alkali-free glass fiber was purchased from Shenzhen Yataida Technology Co., Ltd. (item number: ECS-13-4.5), with a length of 4~5mm and a single fiber diameter of 12~14μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of aluminum oxide was about 10μm.
[0046] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0047] Example 7 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropylmethyldimethoxysilane 5 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 2 parts of aluminum oxide.
[0048] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropylmethyldimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1130; the particle size of alumina was about 10μm.
[0049] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropylmethyldimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and aluminum oxide according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the above mixture to the feeding port of a twin-screw extruder, weigh the above-mentioned weight proportion of alkali-free glass fiber and add it through the fiber feeding port, and extrude it from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0050] Example 8 This embodiment provides a high-strength flame-retardant polyamide 66 composite material and a preparation method thereof. The high-strength flame-retardant polyamide 66 composite material comprises the following components in terms of weight fraction: 75 parts of polyamide 66 resin; 20 parts of alkali-free glass fiber; 3-aminopropyltrimethoxysilane 5 parts; 8 parts of 2-carboxyethylphenylphosphinate; 3 parts of aluminum hydroxide; 2 parts of tritium trioxide.
[0051] Among them, the alkali-free glass fiber was purchased from Shenzhen Tianzhitu Technology Co., Ltd., with a length of 8~12mm and a single fiber diameter of 9~13μm; 3-aminopropyltrimethoxysilane was purchased from Sisibo, with the product number SiSiB® PC1110; the particle size of titanate trioxide is about 10μm.
[0052] The preparation method of the high-strength flame-retardant polyamide 66 composite material comprises the following steps: S1. Fully dry the polyamide 66 resin and the alkali-free glass fiber at 80°C, and weigh the polyamide 66 resin, 3-aminopropyltrimethoxysilane, 2-carboxyethylphenyl hypophosphorous acid, aluminum hydroxide and titanate trioxide respectively according to the above weight fractions, and fully mix them in a high-speed mixer for 3 to 5 minutes; S2. Add the mixture to the feeding port of a twin-screw extruder, weigh the alkali-free glass fiber in the above-mentioned weight proportions and add the fiber through the fiber feeding port, and extrude the fiber from the twin-screw extruder by melt blending, wherein the temperature parameters of zones 1 to 6 of the twin-screw extruder are set as follows during the extrusion process: 230°C, 270°C, 275°C, 275°C, 275°C, 270°C, the die temperature is 275°C, and the screw speed is set to 450 r / min; S3. After extrusion, the extrudate is placed in a vacuum oven at 85°C for 6 hours and molded into various specimens at 280°C.
[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that the preparation raw material 2-carboxyethylphenyl hypophosphorous acid is replaced by diethyl hypophosphorous acid, and the other raw materials and preparation process are the same.
[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that: 2-carboxyethylphenylphosphorous acid is not added to the preparation raw materials, and the weight portion of aluminum oxide is increased to 10 parts, and the other raw materials and preparation processes are the same.
[0055] Comparative Example 3 The difference between this comparative example and Example 1 is that aluminum oxide is not added to the preparation raw materials, and the weight portion of 2-carboxyethylphenyl hypophosphorous acid is increased to 10 parts, and the other raw materials and preparation processes are the same.
[0056] Test Example 1: Combustion Performance Determination This test example measures the combustion performance of the composite material samples prepared in the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 3. Specifically, the composite materials prepared above are respectively prepared into strip samples with a length of 100 mm, a width of 10 mm, and a thickness of 0.4 mm, and then a vertical combustion test is carried out with reference to the standard "GBT2408-2021 Determination of the combustion performance of plastics (horizontal method and vertical method)", as follows: Apply flame to the composite material sample with reference to the national standard. After 10 seconds, evacuate the flame. At the same time, start measuring the afterflame time t1 with a timer in seconds. Record t1 and whether molten droplets or dripping of burning materials occur. If so, indicate whether they ignite the cotton pad.
[0057] When the flame of the sample goes out, immediately re-place the test flame under the sample, keep the central axis of the blowtorch tube in a vertical position and keep the top of the blowtorch about 10 mm below the bottom of the sample for 10 seconds. After applying the flame to the sample for the second time, immediately extinguish the blowtorch and use a timer to start measuring the afterflame time t2 and afterglow time t3 of the sample, accurate to seconds. Note and record, and also record whether there are particles or molten droplets dripping from the sample. If so, observe whether the cotton pad is ignited.
[0058] If one of the five samples treated in the same state does not meet the classification criteria, another group of five samples treated in the same state should be tested. f For V-0, if the total afterflame time is 51s~55s or for V-1 and V-2, if it is 251s~255s, an additional group of five specimens shall be tested. All specimens in the second group shall meet all the criteria specified for that class.
[0059] Repeat 5 samples in each group and take the average value. The rating standard of vertical burning test is shown in the following table.
[0060] Table 1: Vertical burning classification standards
[0061] The vertical combustion performance test results of the composite material samples prepared in the above Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 2.
[0062] Table 2: Vertical combustion performance test results
[0063] The above results show that the flame retardant levels of the high-strength flame-retardant polyamide 66 composite materials prepared in Examples 1 to 8 of the present invention all meet the requirements of relevant flame-retardant materials, and the vertical combustion performance test results thereof reach the V-0 level. Among them, the high-strength flame-retardant polyamide 66 composite materials prepared in Examples 1 and 7 have the best flame retardant performance, and the afterflame time plus the afterglow time (t2+t3) of a single sample after the second application of the flame is as low as 16s; the flame retardant performance of the high-strength flame-retardant polyamide 66 composite material in Example 3 is slightly lower than that of other examples, but still reaches the V-0 level, which is presumably related to the reduction of the flame retardant 2-carboxyethylphenylphosphonic acid. As a highly efficient reactive flame retardant, 2-carboxyethylphenylphosphonic acid helps to form a stable carbonized layer during the combustion process, providing an excellent flame retardant effect.
[0064] Compared with Example 1, in Comparative Example 1, 2-carboxyethylphenyl hypophosphorous acid was replaced with diethyl hypophosphorous acid, and the results showed that its combustion performance was slightly reduced, which is presumably related to its own performance. Diethyl hypophosphorous acid, as a common flame retardant component, can be combined with metal salts such as aluminum hydroxide or magnesium hydroxide to form phosphates to exert a flame retardant effect, and the moisture released during the reaction also helps to improve the flame retardant effect. However, compared with diethyl hypophosphorous acid, 2-carboxyethylphenyl hypophosphorous acid also contains a benzene ring, which is presumably helpful to improve the ability to suppress flames.
[0065] Compared with Example 1, 2-carboxyethylphenyl hypophosphorous acid was not added in Comparative Example 2. The results showed that the flame retardant effect was significantly reduced, and the dripping material ignited the cotton pad during the combustion process, which was presumably related to the formation of phosphate. When 2-carboxyethylphenyl hypophosphorous acid was not added to the system, it could not interrupt the combustion reaction by forming a phosphate protective layer with aluminum hydroxide during the combustion process, thus greatly reducing the flame retardant effect. It can be seen that adding a certain amount of 2-carboxyethylphenyl hypophosphorous acid to the system of the present invention helps to significantly improve the flame retardant effect of the composite material.
[0066] Compared with Example 1, no aluminum oxide was added in Comparative Example 3, and its effect was significantly reduced. In the present invention, aluminum oxide is mainly added as a synergistic flame retardant, which has a synergistic effect with 2-carboxyethylphenyl hypophosphorous acid. On the one hand, it can improve the barrier effect of the carbon layer by changing the carbon slag composition of the composite material, or absorb the heat in the combustion process under high temperature conditions, block the transfer of heat and oxygen, thereby slowing down the combustion process and protecting the composite material; on the other hand, during the combustion process, aluminum oxide can provide thermal isolation and a protective layer, while 2-carboxyethylphenyl hypophosphorous acid can directly participate in the flame retardant process through chemical reactions. This combination can enable the composite material to obtain both physical insulation and chemical flame retardant dual protection in a high temperature environment, and synergistically improve the flame retardant effect.
[0067] Test example 2: Mechanical properties test This test example measures the mechanical properties of the composite material samples prepared in the above examples 1 to 8 and comparative examples 1 to 3, and the control group is polyamide 66 resin. Specifically, the composite materials prepared above are respectively prepared into strip samples with a length of 100 mm, a width of 10 mm, and a thickness of 0.4 mm, and then the tensile properties and bending properties are tested. The specific test method is as follows: (1) Tensile properties test: The tensile properties (including tensile strength and elongation at break) of the composite material samples were tested using an electronic universal testing machine at a test speed of 20 mm / min. The specific method refers to GB / T 1040-2018 standard. (2) Bending performance test: The bending performance (including bending strength and bending modulus) of the composite material samples was tested using an electronic universal testing machine. During the measurement, the instrument operated at a speed of 2 mm / min, the measuring range was 64 mm, and the sensor output power was 500 N. The specific measurement method was referred to GB / T 9341-2008 standard.
[0068] The mechanical properties test results of the above composite materials are shown in Table 3.
[0069] Table 3: Mechanical properties test results
[0070] The above results show that, firstly, the high-strength flame-retardant polyamide 66 composite materials prepared by Examples 1 to 8 of the present invention have excellent mechanical properties, among which the composite material prepared by Example 2 is the best, with a tensile strength of 169.6 MPa and a bending strength of 191.5 MPa. The mechanical properties of the composite material prepared by Example 1 are second, but still significantly improved compared with the comparative example. Secondly, by comparing Example 1 and Example 5, it can be analyzed that when the relative proportions of 2-carboxyethylphenylphosphite, metal hydroxide and synergistic flame retardant are reduced, the mechanical properties are slightly reduced.
[0071] Compared with Example 1, when low aspect ratio alkali-free glass fiber is used (such as Example 6), the mechanical properties of the composite material obtained are reduced, which is presumably related to the decrease in uniformity of stress distribution. The load-bearing area of low aspect ratio alkali-free glass fiber is reduced relative to that of high aspect ratio alkali-free glass fiber.
[0072] In addition, it is worth noting that in the composite material of the present application scheme, the mechanical properties of the 3-aminopropyl trimethoxy silane coupling agent are relatively higher than those of the 3-aminopropyl methyl dimethoxy silane coupling agent (reference examples 1 and 7), which is speculated to be related to the methoxy functional group (-OCH3). The 3-aminopropyl methyl dimethoxy silane coupling agent contains three methoxy functional groups, while the 3-aminopropyl methyl dimethoxy silane coupling agent contains only two methoxy functional groups. The methoxy functional groups can react with the glass fiber to form siloxane bonds (-Si-O-Si), thereby promoting the formation of a stable siloxane network, which helps to improve the mechanical properties of the composite material. In addition, since the aminosilane coupling agent contains amino functional groups, these amino functional groups can form hydrogen bonds or covalent bonds with polar functional groups such as carboxyl (-COOH) and hydroxyl (-OH) on the surface of other components, which helps to further improve the interface bonding strength and stability.
[0073] Compared with Example 1, in Comparative Example 1, 2-carboxyethylphenyl hypophosphorous acid was replaced with diethyl hypophosphorous acid. The results showed that its mechanical properties were significantly reduced, with the tensile strength reduced by 9.65% and the bending strength reduced by 6.06%. It is speculated that this is related to the lack of carboxyl functional groups. 2-carboxyethylphenyl hypophosphorous acid contains carboxyl functional groups, which help to improve the adhesion and interfacial compatibility of the interface, thereby promoting the improvement of mechanical properties.
[0074] Compared with Example 1, no 2-carboxyethylphenylphosphorous acid was added in Comparative Example 2, and no aluminum oxide was added in Comparative Example 3. It can be seen from the above test results that the mechanical properties are significantly reduced, which is presumably related to the reduction in interfacial properties. When 2-carboxyethylphenylphosphorous acid is lacking in the system, the interfacial properties between polyamide 66 and glass fiber will be reduced.
[0075] In summary, the present invention provides a high-strength flame-retardant polyamide 66 composite material, a preparation method and application thereof. The polyamide 66 composite material prepared by compounding an aminosilane coupling agent, a metal hydroxide, 2-carboxyethylphenylphosphorous acid and aluminum trioxide (or antimony trioxide) not only has excellent mechanical properties, but also has a vertical combustion grade of V-0, and has broad application prospects.
[0076] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A polyamide 66 composite material, characterized in that: The raw materials for preparation include the following components: Polyamide 66 resin, glass fiber, aminosilane coupling agent, 2-carboxyethylphenylphosphorous acid, metal hydroxide, synergistic flame retardant, wherein the synergistic flame retardant is selected from any one of aluminum oxide and antimony trioxide.
2. The polyamide 66 composite material according to claim 1, characterized in that: The raw materials include the following components by weight: 60-85 parts of polyamide 66 resin; Glass fiber 10~30 parts; 3-8 parts of aminosilane coupling agent; 5-10 parts of 2-carboxyethylphenyl hypophosphorous acid; 3~8 parts of metal hydroxide 1~5 parts of synergistic flame retardant.
3. The polyamide 66 composite material according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber; Preferably, the alkali-free glass fiber has a length of 3 to 15 mm and a single fiber diameter of 8 to 15 μm.
4. The polyamide 66 composite material according to claim 1, characterized in that: The aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane and aminoethylaminopropylmethyldiethoxysilane.
5. The polyamide 66 composite material according to claim 1, characterized in that: The metal hydroxide is selected from at least one of aluminum hydroxide, calcium hydroxide, magnesium hydroxide and zinc hydroxide.
6. The polyamide 66 composite material according to claim 1, characterized in that: The particle size of the synergistic flame retardant is 1-20 μm.
7. A method for preparing the polyamide 66 composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing the polyamide 66 resin, aminosilane coupling agent, 2-carboxyethylphenylphosphite, metal hydroxide and synergistic flame retardant to obtain a mixture; S2, extruding the mixed material and the glass fiber using a twin-screw extruder.
8. The preparation method according to claim 7, characterized in that: The temperatures of zones one to six of the twin-screw extruder are 220-240°C, 260-280°C, 265-285°C, 265-285°C, 265-285°C, and 260-280°C, respectively.
9. The preparation method according to claim 8, characterized in that: The screw speed of the twin-screw extruder is 350-550 r / min.
10. Use of the polyamide 66 composite material according to any one of claims 1 to 6 in the preparation of automobile or building materials.
Citation Information
Patent Citations
Environment-friendly flame retardant glass fiber reinforced polyamide 66 (PA66) material with high comparative tracking index (CTI) value and high glow wire ignition temperature (GWIT) value and preparation method thereof
CN102952399A
Insulated and flame-retardant nylon composite material with high thermal conductivity and preparation method thereof
CN103788642A
High-GWIT flame-retardant PBT composition and preparation method and application thereof
CN112795147A
Long glass fiber PP with stable flame-retardant structure and preparation method thereof
CN114854131A
High-performance low-warpage halogen-free flame-retardant reinforced PA66 composite material and preparation method thereof
CN116790119A